Les nouveaux modes de déplacement individuel doux basés sur l’électrique. Attractivité et insertion modale - Thibaud Pages; Adrien Lammoglia; Didier Josselin (Territoire en Mouvement)
This paper is part of a research program funded by the Provence-Alpes-Côte d’Azur (PACA) region that focuses on mobility practices for the 2030 and 2050 horizons. Transport is a sector in constant evolution. Recently, we observed the rise of the new individual electric vehicles (NIEV) in our cities. These vehicles are part of today’s mobility, and certainly tomorrow’s, due to the use of electric energy. This makes them attractive in the context of reducing carbon emissions in urban centers. In the spring of 2020, France experienced a lockdown related to the Covid-19 health crisis. The unlock, considered "risky", obliged politicians to urgently set up temporary cycling paths that are also used by NIEV. These vehicles appear to be the most advantageous in terms of social distancing, unlike public transport. This sudden increase in temporary infrastructures, some of which will become permanent, suggests that it will reinforce the growth of NIEV in urban areas.In order to better understand the growth of NIEV, an online survey was shared during April and May 2020. The objective of this survey is to better understand the users and uses of these vehicles. The survey is also intended for non-users who are in direct contact with NIEV users. The survey questions the opinion on the preservation of the environment, the necessary arrangements concerning these vehicles, etc. At the end of May 2020, the survey gets 250 responses, including 120 NIEV users. In addition, interviews were conducted to obtain qualitative data.The results of the survey identified several environmental and urban planning issues. For example, 68.3% of users are convinced that NIEV are environmentally friendly. In addition, 84.2% of users consider them to be practical and useful in urban areas. The open-ended questions and interviews shed light on ideas for improvements to these new transports. Indeed, many users and non-users report difficulties for NIEV to circulate in urban areas. These vehicles have not yet found a suitable place to circulate and are often circulating on sidewalks, cycling paths, or even on the road.